Pengaruh Ukuran Umbi terhadap Pertumbuhan Awal Tiga Varietas Bawang Merah (Allium ascalonicum L.) - Susilawati, Susilawati; Sodikin, Erizal; Sulaiman, Firdaus; Irmawati, Irmawati (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Susilawati, S., Sodikin, E., Sulaiman ,F., & Irmawati, I. (2023). The effect of bulb size on the initial growth of three varieties of shallot (Allium ascalonicum L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 151-162). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Both vegetative (using bulbs as planting material) and generative (using seeds) methods can be used to cultivate shallot plants. Although using bulbs is simpler, it has a number of drawbacks, including the need for more seeds, relatively high costs, and the challenge of planning a planting timetable. In order to support the growth of three types of shallots, this study sought to assess the strength of the correlation and regression models of the bulb features. The study was carried out during June and July 2023 in Tanjung Pering Village, Indralaya Utara Subdistrict, Ogan Ilir, South Sumatra, at coordinates 003 13'00